2/3(x-6)=14

1 answer

To solve the equation 2/3(x-6) = 14, we can start by distributing the 2/3 to the terms inside the parentheses:

(2/3)(x-6) = 14

(2/3)x - (2/3)(6) = 14

(2/3)x - 12/3 = 14

Now, we can simplify the equation by converting 12/3 to 4:

(2/3)x - 4 = 14

Next, we can isolate the x-term by adding 4 to both sides of the equation:

(2/3)x - 4 + 4 = 14 + 4

(2/3)x = 18

Finally, we can solve for x by multiplying both sides of the equation by the reciprocal of 2/3, which is 3/2:

(3/2)*(2/3)x = (3/2)*18

x = 27